2010
DOI: 10.1016/j.mrrev.2010.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 2/16 estrogen metabolite ratio levels in healthy women: A review of the literature

Abstract: This is a summary of the published literature on the urinary 2/16 estrogen metabolite ratio in human populations, and a report the observed range of normal values in healthy women. Original research studies that included the measurement of urinary estrogen metabolites in human subjects were identified through an extensive Medline search; 43 distinct studies were indentified, including a total of 6802 healthy women. The range of mean values of the 2/16 ratio measured with the ELISA method varied from 0.98 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 93 publications
1
9
0
Order By: Relevance
“…Menopausal status did not strongly affect EMR in most studies, which is compatible with the observed overlapping distributions of EMR in pre- and postmenopausal women 32. Genetic makeup and differential activity of metabolizing hydroxylases and other enzymes (eg, COMT) have been estimated to explain most of the variation in EMR 65.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Menopausal status did not strongly affect EMR in most studies, which is compatible with the observed overlapping distributions of EMR in pre- and postmenopausal women 32. Genetic makeup and differential activity of metabolizing hydroxylases and other enzymes (eg, COMT) have been estimated to explain most of the variation in EMR 65.…”
Section: Discussionsupporting
confidence: 73%
“…Although little evidence indicates that EMR is associated with a family history59 or benign breast disease, circulating EMR has been shown to increase during the menstrual cycle 60. Urinary estrogen metabolite levels vary strongly by ethnicity, showing lowest mean values in healthy African Americans followed by Asians and Caucasians 32,45,6164. Although ethnic variations in plasma EMR were less pronounced,55 uncontrolled confounding could have masked, diluted, or even pretended a potential EMR effect in studies not adjusted for ethnicity depending on the combination of case-control pairs (even if percentages [other than for Caucasians] were as low as 12%–16%) 38,43.…”
Section: Discussionmentioning
confidence: 99%
“…However, these findings can not be generalized, as there may be heterogeneity in the population. Importantly, after adjustments are made for age and menopausal status, only race could be a predictor of 2-OH-E1/16α-OH-E1 ratio, and hence systolic blood pressure, as the 2-OH-E1 levels are significantly higher during the follicular phase and mid-cycle among African-American compared with Caucasian women [37,38]. …”
Section: Mht Pharmacokineticsmentioning
confidence: 99%
“…The major metabolite of estradiol is 2-hydroxyestrone (2OHE), which has a weak effect on the estrogen receptor, and a positive role as cardiovascular protector [10,11]. In humans, another important EM is the 16-hydroxyestrone (16OHE), which has been associated with a risk of breast and endometrial cancer [12].…”
Section: Introductionmentioning
confidence: 99%